The forgotten man : a new history of the great depression - Shlaes, Amity (New York, 2008)
"In The Forgotten Man, Amity Shlaes, one of the nation's most-respected economic commentators, offers a striking reinterpretation of the Great Depression. She traces the mounting agony of the New Dealers and the moving stories of individual citizens who through their brave perseverance helped establish the steadfast character we recognize as American today. "